Make it or break it: Conflict in coach-athlete relationships - Wachsmuth, S.; Jowett, S.; Harwood, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The coach-athlete relationship plays a central role in sport performance (Jowett & Shanmugam, in press). However, as in every relationship, conflict is inevitable and needs to be managed effectively. Despite its practical relevance in everyday coaching, research has failed to contribute a systematic scientific basis from which to examine conflict processes, determinants and consequences of interpersonal conflict. Recently, empirical efforts to study conflict have been noted around conflicts within sport teams (Partridge et al., 2015); organizations (Kerwin et al., 2011) or fan groups (Schumacher Dimech et al., 2016). The current study aims to provide a comprehensive account of interpersonal conflict within coach-athlete dyads through elite coaches` perspectives. Methods: A total of eleven coaches from team (n=8) and individual (n=3) sports participated in the study. Coaches` performance level ranged from national (n=5) to international (n=6). The interview guide consisted of 26 open-ended questions that were classified in four categories: 1) Introduction/ Coaching Experience (5); 2) Interpersonal Conflict/ Concept (2); 3) Conflict Experience (9); and 4) Determining Factors/ Outcomes (10). The semistructured interviews lasted from 48 minutes to over 2 hours and 14 minutes. All interviews were transcribed verbatim and a cross-case content analyses was conducted (Krippendorff, 1989). Ethical approval for carrying out the study was obtained from the researchers` institution. Results: In total, three higher-order themes were derived from the data, covering the following areas: 1) Determining Factors and Conflict Circumstances; 2) Interpersonal Conflict as a Process; and 3) Conflict Consequences. Discussion: This study provides an indepth insight into the experiences of conflict within the context of the coach-athlete relationship. The results shed light in the ways coaches perceive interpersonal conflict as well as the influences of conflict in their emotions, thought processes and behaviors. Moreover, the results suggest that conflict can be both a facilitative and a debilitative process. Finally, the results provide initial practical suggestions concerning strategies that may minimize the negative effects of interpersonal conflict. The current study paves the way for more research in a significant yet underdeveloped psychosocial area. ABSTRACT FROM AUTHOR